Association between cataract and cotinine-verified smoking status in 11 435 Korean adults using Korea National Health and Nutrition Examination Survey data from 2008 to 2016. Issue 1 (January 2020) - Lee, Hae Jeong; Kim, Cheol Hong; Lee, Ju Suk; Kim, Sung Hoon
Abstract : Purpose: To investigate the association between cataract and cotinine-verified smoking status. Setting: Samsung Changwon Hospital, Sungkyunkwan University School of Medicine, South Korea. Design: Retrospective study. Methods: Participants were randomly selected using data collected by the Korea National Health and Nutrition Examination Survey from 2008 to 2016. Participants completed a questionnaire to self-report smoking status and a history of cataract, among other variables. To identify the relationship between cataract and smoking, a new variable was used to define smoking status, survey-cotinine-verified smoking status (SCS)—the combination of self-reported smoking status and cotinine-verified smoking status– and thus identify hidden smokers. Results: In total, 11 435 participants were eligible for final analysis. The study comprised 4925 men and 6510 women; the mean age was 52.86 ± 16.83 years (median: 54 years). Of 2292 SCS smokers, 382 (16.7%) were nonsmokers according to their self-report. Notably, the ratio of the cotinine-verified to self-reported smoking rate of women was greater than that of men, 1.60 and 1.06, respectively. This indicated that female hidden smokers may affect the results of studies based on self-reported questionnaires. Multivariate logistic regression analysis showed that smoking was correlated with cataract (odds ratio [OR], 1.37 [95% CI, 1.07-1.76]; OR, 1.35 [CI, 1.12-1.64]; and OR, 1.36 [CI, 1.10-1.69]) for self-reported, cotinine-verified, and SCS, respectively. No statistically significant sex difference was found. Conclusion: Smoking was associated with cataract, but it did not vary by sex. Female hidden smoking must be considered when investigating the association between smoking and cataract based on self-reported questionnaires. Abstract : To identify the relationship between cataract and smoking, a new variable was created to define smoking status (survey-cotinine-verified smoking status). Smoking, including female hidden smoking, is associated with cataract.